SIZE TREND ANALYSIS OF BIGEYE TUNA (Thunnus obesus) AND YELLOWFIN TUNA (Thunnus albacares) AT PALABUHANRATU ARCHIPELAGO FISHING PORT - Dita Agustian; Erri Noviar Megantara; Yudi Nurul Ihsan; Martha Fani Cahyandito (JFMR (Journal of Fisheries and Marine Research), 2021)
Bigeye tuna (Thunnus obesus) and Yellowfin tuna (Thunnus albacares) are a marine commodity that has high nutritional content and economic value in the market. However, based on data from Palabuhanratu Archipelago Fishing Port, there has been a high decrease in the catch of Bigeye tuna and Yellowfin tuna since 2016 although slightly increased in the following year, so it is necessary to analyze the size trends of them as a target fish of many fishermen at the port. The purpose of this study is to determine the size trend of Bigeye and Yellowfin tuna for the next few years and to determine the steps to maintain their sustainability. The method used in this research is a case study and analyzed using regression analysis. The results showed that the size trend of Bigeye tuna and Yellowfin tuna catch until 2022 will tend to decline. This indicates the occurrence of overfishing so that it does not provide opportunities for fish to grow and develop. Therefore, catch control efforts are needed to maintain the sustainability of fish stocks.